2022
DOI: 10.9734/jerr/2022/v23i517612
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Chemical Analysis of Different Brands of Cements used in Ghana

Abstract: In Ghana, however, ordinary Portland-limestone cement in recent times continues to remain the alternative construction material compared to other brands. With the rising trend of infrastructural development in the country undertaken by individuals and real estate companies, there have been categories of different brands of cement alongside the existing brands being produced in Ghana. The usage of lowquality cement resulting in poor bonding of construction materials has led to the investigation of some selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The quality of cement is an essential phenomenon as it materially contributes to the strength and durability of the structure over time. Previous research by Akyen and Kankam [20] found significant variations in the chemical compositions among the various brands of cements in Ghana. These chemical compounds and their contents in the cements are illustrated in Tables 1 (a to d).…”
Section: Introductionmentioning
confidence: 87%
“…The quality of cement is an essential phenomenon as it materially contributes to the strength and durability of the structure over time. Previous research by Akyen and Kankam [20] found significant variations in the chemical compositions among the various brands of cements in Ghana. These chemical compounds and their contents in the cements are illustrated in Tables 1 (a to d).…”
Section: Introductionmentioning
confidence: 87%
“…The development of cracks in concrete structures can largely be attributed to the poor setting time of concrete which makes them less durable to withstand stresses imposed on them [3,4]. As a result, many researchers have conducted investigations and observed that most chemical compositions of cement are not adequately proportioned to perform the requisite functions of cements [5][6][7][8]. The chemical compositions play vital role in the setting time and strength of both cement and concrete and insufficient quantity in the mix could lead the concrete to achieve poor strength.…”
Section: Introductionmentioning
confidence: 99%
“…In order to use concrete efficiently for construction in Ghana, it is important to look at the effects of the different types of cement available on the market. For these reasons, previous works investigated the effects of chemical composition of concrete made from the cements [6,7,30]. The aim of the project study was to look at the impact of a few specific brands of cement that are used for different types of infrastructure construction in Ghana on the properties of fresh cement paste and concrete.…”
Section: Introductionmentioning
confidence: 99%